Design of a digital beam attenuation system for computed tomography: Part I. System design and simulation framework. Issue 2 (16th January 2013) - Szczykutowicz, Timothy P.; Mistretta, Charles A.
Abstract : Purpose: : The purpose of this work is to introduce a new device that allows for patient‐specific imaging‐dose modulation in conventional and cone‐beam CT. The device is called a digital beam attenuator (DBA). The DBA modulates an x‐ray beam by varying the attenuation of a set of attenuating wedge filters across the fan angle. The ability to modulate the imaging dose across the fan beam represents another stride in the direction of personalized medicine. With the DBA, imaging dose can be tailored for a given patient anatomy, or even tailored to provide signal‐to‐noise ratio enhancement within a region of interest. This modulation enables decreases in: dose, scatter, detector dynamic range requirements, and noise nonuniformities. In addition to introducing the DBA, the simulation framework used to study the DBA under different configurations is presented. Finally, a detailed study on the choice of the material used to build the DBA is presented. Methods: : To change the attenuator thickness, the authors propose to use an overlapping wedge design. In this design, for each wedge pair, one wedge is held stationary and another wedge is moved over the stationary wedge. The composite thickness of the two wedges changes as a function of the amount of overlap between the wedges. To validate the DBA concept and study design changes, a simulation environment was constructed. The environment allows for changes to system geometry, different source spectra, DBA wedge design modifications, and supports both voxelized and analytic phantom models. A study of all the elements from atomic number 1 to 92 were evaluated for use as DBA filter material. The amount of dynamic range and tube loading for each element were calculated for various DBA designs. Tube loading was calculated by comparing the attenuation of the DBA at its minimum attenuation position to a filtered non‐DBA acquisition. Results: : The design and parametrization of DBA implemented FFMCT has been introduced. A simulation framework was presented with which DBA‐FFMCT, bowtie filter CT acquisitions, and unmodulated CT acquisitions can be simulated. The study on wedge filter design concluded that the ideal filter material should have an atomic number in the range of 21–34. Iron was chosen for an experimental relative‐tube‐loading measurement and showed that DBA‐FFMCT scans could be acquired with negligible increases in tube power demands. Conclusions: : The basic idea of DBA implemented fluence field modulated CT, a simulation framework to verify the concept, and a filter selection study have been presented. The use of a DBA represents another step toward the ultimate in patient specific CT dose delivery as patient dose can be delivered uniquely as a function of view and fan angle using this device.